(3GdhSjW aj MeGjI Mbhb GdedcjI GdacQjI hLhGFR GdOhdI aj GdYdhe hGdYdhe GdJcfhdhLjI GdeJbOeI hGdafhf hGdBOGH ddeHOYjf hGdeJahbjfs - (3GdSjO YHO GdhgGH(B, (3YQaIs ((3GdEScfOQjI(B:s (3OGQ GdeWHhYGJ GdLGeYjI(B,s, 2004)
(3GdHQGAI hGdWHjYI GdbGfhfjI dgG , HQGAI fehPL GdefaYI, GdJUejeGJ GdJNWjWjI ddOhGFQ GdeJcGedI , GdeYdheGJ ZjQ GdeaUM YdjgG(B( (3GdeYdheGJ GdSQjI(B)(3, GdYdGeI GdJLGQjI, GdHjGf GdJLGQj, GdeDTQGJ GdLZQGajI, GdEJaGbjGJ GdOhdjIs
Keywords: (3GdEJaGbjGJ GdOhdjIs; (3GdMeGjI GdbGfhfjIs; (3Mbhb GdedcjIs